Personal librarians : building relationships for student success - Bisko, Lynne; Buchansky, Heather; Gray, Brian C.; Reese, Elaine (Libraries Unlimited, 2019)
In order to get the most out of their research, students need to understand the depth of resources and services available to them. Personal librarian programs help students--especially new ones--to feel welcome in the library and comfortable asking for assistance. They provide enhanced support and serve as students' point of contact to help them build the information literacy skills necessary to successfully navigate their academic path. Personal Librarians: Building Relationships for Student Success focuses on specific ways to connect with and to engage first-year and other new-to-campus students. The authors provide concrete guidance, informed by interviews with other librarians who have successfully implemented such programs, for librarians wishing to begin or expand programs of their own. Personal librarian programs provide opportunities for the proactive to build relationships that grow student confidence as future needs arise--and the authors, who coordinate personal librarian programs at their own institutions, demonstrate how well they work.